THE SUSPENSION OF THE COLLECTION OF INTEREST ON LATE PAYMENTS IN THE FISCAL ADMINISTRATIVE PROCESS AFTER THE TRANSACTION OF THE TERM DETAILED IN ARTICLE 24 OF LAW Nº. 11.457/2007 - Carolina Silveira; João Glicério de Oliveira Filho (Revista Eletrônica de Direito Processual, 2020)
This text is a brief reflection on the demand for late payment interest in the course of the tax administrative process after the expiry of the legal period of 360 days that art. 24 of Law No. 11,457 / 07 grants for the Public Administration to make a decision on the defenses presented by taxpayers due to the constitution of a tax credit. The analysis will be by through bibliographic research and normative analysis. The first part deals with the time limit for constant judgment in the legislation, inversion of arrears, compliance with the principle of symmetry and the need to apply sanctions. The second part analyzes the jurisprudence and the principles that must be observed by the Public Administration. The end, it is unlawful to collect default interest after the statutory period has elapsed for the public administration to judge the defenses presented by taxpayers in the course of the fiscal administrative process.